Static and random vibration analysis of an air freight package. Issue 3 (May 2021) - Diao, Jiandong; Huang, Qiushuang; Pan, Yang; Zhang, Chenfeng
Abstract: Due to the significant speed advantage, air freight has become the preferred long-distance transportation method for precision electronic instruments and other high-value products. In order to avoid the impact of air load conditions on the safety of cargo and aircraft, it is necessary to calculate and check the carrying capacity of cargo package. In this paper, finite element analysis has been applied on design of an air freight package. Firstly, make force analyze, and use the maximum force for static analysis to solve stress distribution. Then, make modal analysis and random vibration analysis to obtain the 3σ stress and deformation. According to static analysis, the maximum equivalent stress of the package under emergency conditions is less thanσb . According to dynamic analysis, the probability that the maximum stress of the package is greater than 56.69Mpa does not exceed 0.3%.